2009
DOI: 10.1182/blood-2009-04-217620
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of the alternatively activated macrophage phenotype

Abstract: Alternatively activated (M2) macrophages play critical roles in diverse chronic diseases, including parasite infections, cancer, and allergic responses. However, little is known about the acquisition and maintenance of their phenotype. We report that M2-macrophage marker genes are epigenetically regulated by reciprocal changes in histone H3 lysine-4 (H3K4) and histone H3 lysine-27 (H3K27) methylation; and the latter methylation marks are removed by the H3K27 demethylase Jumonji domain containing 3 (Jmjd3). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
390
2
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(410 citation statements)
references
References 47 publications
12
390
2
6
Order By: Relevance
“…33 Several other studies have also shown that M1 classical responses and NO production do not differ between wild-type and Jmjd3-deficient macrophages. 33,34 However, our findings have revealed that Figure 5 Arginase1 prevents neuron death through counteracting iNOS. (a) N9 cells were infected with pLKO-kdNC, pLKO-kdJmjd3, pLKO-kdArginase1 lentiviruses, as well as pLKO-kdJmjd3/pLVX-Arginase1 mixed lentiviruses.…”
Section: Discussionmentioning
confidence: 78%
“…33 Several other studies have also shown that M1 classical responses and NO production do not differ between wild-type and Jmjd3-deficient macrophages. 33,34 However, our findings have revealed that Figure 5 Arginase1 prevents neuron death through counteracting iNOS. (a) N9 cells were infected with pLKO-kdNC, pLKO-kdJmjd3, pLKO-kdArginase1 lentiviruses, as well as pLKO-kdJmjd3/pLVX-Arginase1 mixed lentiviruses.…”
Section: Discussionmentioning
confidence: 78%
“…Lung alveolar macrophages (Lin et al, 2008) play a pivotal role in the pathogenesis of ALI, and plasticity of M1 and M2 macrophages takes place because of bacterial products, which -in turn -result in the inflammation of lung tissue. M2 macrophages are involved in tissue repair and remodeling (Ishii et al, 2009;Wynn, 2004). The genes expressed by the macrophages can be phenotypically characterized as M1 (inflammatory) and M2 (anti-inflammatory) macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 CHI3L3 was described as typical marker of M2 macrophages in mice. 31 According to our results, CHI3L1 pseudochitinase is the corresponding counterpart in humans where it constitutes an important regulator of inflammation, angiogenesis and M2 macrophage differentiation in addition to its expression by SCLC CTCs. 12,32 Specifically, M2b macrophages are activated by immune complexes, toll-like receptor-positive lymphocytes, or IL-1ra.…”
Section: Secretory Phenotype Of Sclc Ctc-induced Macrophagesmentioning
confidence: 99%